Cerebral toxoplasmosis complicating lymphoplasmacytic lymphoma in partial remission. Issue 2 (February 2022) - Murakami, Daisuke; Maki, Hiroaki; Matsuda, Kensuke; Masamoto, Yosuke; Suzuki, Fumio; Amemiya, Shiori; Osawa, Kazuhiro; Hinata, Munetoshi; Ikemura, Masako; Ushiku, Tetsuo; Kurokawa, Mineo
Abstract: Toxoplasma gondii can develop toxoplasmic encephalitis (TE) in immunodeficient conditions such as AIDS and after organ transplantation. While some cases of TE with malignant lymphoma were reported, these cases occurred immediately after chemotherapy or when their diseases were active. Here we report the first Case of TE that occurred in patient who was in partial remission (PR) of lymphoplasmacytic lymphoma (LPL) for two years. A 76-year-old man was referred to our institute because of disturbance of consciousness, right arm weakness and paresthesia. A computed tomography (CT) scan detected multiple nodules in his brain. Magnetic resonance imaging (MRI) of the head detected multiple gadolinium-enhancing parenchymal lesions with hyperintense signals on T2-and diffusion-weighted images, located in both cerebral and cerebellar hemispheres. Blood test and cerebrospinal fluid (CSF) findings were unremarkable. His rapidly deteriorating consciousness precluded a chance of brain biopsy. Considering the limited efficacy of antimicrobials and the imaging findings that could be compatible with the diagnosis of malignant lymphoma, we suspected central nerve system (CNS) recurrence of LPL. Although chemotherapy was initiated, he died of respiratory failure just after chemotherapy. A pathological autopsy showed his cause of death was TE. To our knowledge, this is the first case of TE in long-term PR of malignant lymphoma. TE should be suspected when patients with malignant lymphoma present unexplained neurologic symptoms regardless of their treatment efficacy of lymphoma. (226/250 words).